2018
DOI: 10.1007/s11427-017-9156-1
|View full text |Cite
|
Sign up to set email alerts
|

The S190R mutation in the hemagglutinin protein of pandemic H1N1 2009 influenza virus increased its pathogenicity in mice

Abstract: Human influenza viruses preferentially bind to sialic acid-α2,6-galactose (SAα2,6Gal) receptors, which are predominant in human upper respiratory epithelia, whereas avian influenza viruses preferentially bind to SAα2,3Gal receptors. However, variants with amino acid substitutions around the receptor-binding sites of the hemagglutinin (HA) protein can be selected after several passages of human influenza viruses from patients' respiratory samples in the allantoic cavities of embryonated chicken eggs. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…As the original B/Phuket/3073/2013 vaccine strain was passaged in embryonated eggs, we identified in its HA protein the N196D egg-adapted substitution that could potentially increase viral pathogenicity in mice through adaptation to a α2,3 sialic acid receptor. A similar role was previously attributed for the S190R A(H1N1) egg-adapted HA mutation [33,34].…”
Section: Discussionsupporting
confidence: 76%
“…As the original B/Phuket/3073/2013 vaccine strain was passaged in embryonated eggs, we identified in its HA protein the N196D egg-adapted substitution that could potentially increase viral pathogenicity in mice through adaptation to a α2,3 sialic acid receptor. A similar role was previously attributed for the S190R A(H1N1) egg-adapted HA mutation [33,34].…”
Section: Discussionsupporting
confidence: 76%
“…The mechanism of egg adaptation was illustrated early [21,22]. It was shown that the S190R variant of the A/Hunan/26/2016 (H1N1)pdm09 virus had increased pathogenicity in mice [21]. However, in our study, the presence of this component in the population of the virus did not increase its pathogenicity (Figure 5).…”
Section: Discussionmentioning
confidence: 48%
“…In addition, the R variant is usually a result of egg adaptation. The mechanism of egg adaptation was illustrated early [21,22]. It was shown that the S190R variant of the A/Hunan/26/2016 (H1N1)pdm09 virus had increased pathogenicity in mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…Using CA04 strain-based HA mutants generated by reverse genetics, we identified the S190R substitution in the antigenic site Sb of HA as one of the critical determinants for the differential HA antigenicity of A(H1N1)pdm09-related swIAVs (). It should be noted that the S190R substitution in HA was previously reported as an egg-adapted mutation of human A(H1N1)pdm09 viruses [63], although A/swine/Aichi/KU-OE7/2017 (H1N2), which is the only isolate possessing the S190R substitution in HA among all the A(H1N1)pdm09-related human and swine viruses available in the GISAID database (), was isolated in canine-origin AX4 cells. Importantly, we confirmed by nucleotide sequencing that the HA gene segment detected in the original specimen for A/swine/Aichi/KU-OE7/2017 (H1N2) indeed encoded arginine at amino acid position 190 (data not shown).…”
Section: Discussionmentioning
confidence: 99%